(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Pot experiments were carried out with rice (Oryza sativa L.) to evaluate the plant response of different amendments to ameliorate heavy metal toxicity. Cowdung and lime were applied at the rate of 10 ton/ha. Both cowdung and lime application led to an increase in growth of rice and significant reductions of Zn, Ni, Cu and Cr in plant. The length, fresh and dry weight and N, P, K, Na, Ca and Mg concentrations in rice plants were increased significantly. The concentrations of Cu, Zn, Ni, Pb and Cr in rice grown on contaminated soils were significantly higher as compared to the control. Cowdung and lime significantly reduced Cu, Zn, Ni, Pb and Cr concentrations in comparison to control. Chromium concentrations in lime treated plants were reduced by 57.89% in rice as compared to cowdung. Lime proved to be more efficient in reducing the concentration of metals in rice plants. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 47-54